2023
DOI: 10.1001/jama.2023.20850
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Resuscitative Endovascular Balloon Occlusion of the Aorta in Trauma Patients With Exsanguinating Hemorrhage

Jan O. Jansen,
Jemma Hudson,
Claire Cochran
et al.

Abstract: ImportanceBleeding is the most common cause of preventable death after trauma.ObjectiveTo determine the effectiveness of resuscitative endovascular balloon occlusion of the aorta (REBOA) when used in the emergency department along with standard care vs standard care alone on mortality in trauma patients with exsanguinating hemorrhage.Design, Setting, and ParticipantsPragmatic, bayesian, randomized clinical trial conducted at 16 major trauma centers in the UK. Patients aged 16 years or older with exsanguinating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
49
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 33 publications
0
49
0
1
Order By: Relevance
“…To the Editor A recent randomized clinical trial on REBOA showed that use of the technique may be detrimental to patients in some major trauma centers in the UK. However, I have some concerns about this study.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…To the Editor A recent randomized clinical trial on REBOA showed that use of the technique may be detrimental to patients in some major trauma centers in the UK. However, I have some concerns about this study.…”
mentioning
confidence: 58%
“…However, in this study, balloon dilation was performed in only 19 of 46 patients (41%) making it difficult to examine its true effect on complications. REBOA insertion may have delayed standard care because the time to a definitive hemorrhage control procedure was longer in the REBOA and standard care group vs the standard care alone group …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Reply We thank the authors for the letters about our recently published randomized clinical trial of emergency department REBOA in trauma patients …”
mentioning
confidence: 99%
“…In another original report, Jansen and colleagues tested an approach to limit uncontrolled hemorrhage in trauma: temporary aortic occlusion with the resuscitative endovascular balloon (REBOA). Amidst position statements and observational studies, the authors successfully performed the first randomized trial in humans of REBOA in traumatic injury.…”
mentioning
confidence: 99%